Pleomorphic Adenoma of the Nasal Vestibule – A Rare Case - Matin, MA; Haque, Enamul; Md Asafuddoula, -; Ghosh, Subroto; Hossain, Mahmud (Bangladesh Journal of Otorhinolaryngology, 2020)
Pleomorphic adenomas arising in the nasal cavity are extremely uncommon, despite the large numbers of minor mucous and serous glands in the region. We present a rare case of a pleomorphic adenoma arising from the right nasal vestibule in a 65-year-old man complained of right nasal obstruction for 6 months. Anterior rhinoscopy showed a reddish, firm, polypoid mass in right nasal cavity which is free from the nasal septum and from the inferior tubinate but it was attached to the nasal vestibule. Flexible nasal endoscopy showed no extension of the mass towards the posterior choana or nasopharynx. The mass was completely excised from the nasal vestibule through intranasal approach and sent for histology which confirmed a pleomorphic adenoma with a predominant stromal component. The main treatment modality is surgical resection with histological clear margins. Recurrences and evolution to malignancy are not frequent, but long tern follow-up is recommended. In our case, the patient demonstrated satisfactory cosmetic results with no evidence of recurrence. Bangladesh J Otorhinolaryngol; April 2017; 23(1): 88-91